A Conceptual Framework for Research in Music and Music Education within a Cultural Context - Akuno, Emily Achieng ' (Bulletin of the Council for Research in Music Education, 2000)
Music education in Kenya has been, and continues to be conducted along Western theories which fall short of defining music as experienced within traditional African cultures (New, 1980; Omondi, 1980; Kwami, 1989; Akuno, 1997; Kidula, 1998). Research in music, an attempt to find reality and meaning in it, involves discovering its components, how they make a cohesive and comprehensible whole, and how the produced item functions in the economy of the culture thai produces and consumes it. Since music must be understood from the participants 'point of view, a true understanding involves analysis within the context in which it is created and practised. The created music is influenced by the artist's understanding of the subject through experience and knowledge gained in that genre. Such experience, gained from casual, informal contacts or deliberate, organised instruction, is drawn upon for musical creativity as manifested in performance, response to musical stimuli as well as composition. This paper examines this process to come up with a conceptual framework for the understanding of music within a cultural context.
Keywords: Music Education